Genomic insights into multidrug-resistant mammaliicoccus sciuri carrying novel staphylococcal cassette chromosome mec (SCCmec) elements and plasmids from farm ruminants on the East Coast of Peninsular Malaysia - Megat Zakaria, Puteri Nazurah; Lean, Soo Sum; Mohd Desa, Mohd Nasir; Aklilu, Erkihun; Shamsir Omar, Mohd Shahir; Yeo, Chew Chieng; Suhaili, Zarizal (Springer, 2025)
Mammaliicoccus sciuri (formerly known as Staphylococcus sciuri) are Gram-positive bacteria that were previously considered as commensals but has since been reported to cause mild to severe infections in both animals and humans. Since very little is known regarding M. sciuri isolates from Malaysia, this study aims to characterise the genomes of four M. sciuri isolates obtained from the nasal swabs of farm ruminants in the eastern coast states of Kelantan and Terengganu in Peninsular Malaysia. Presumptive M. sciuri isolates were validated using MALDI-TOF and antimicrobial susceptibility testing were performed using disc diffusion. The four multidrug-resistant M. sciuri isolates were subjected to both short- and long-read genome sequencing using the Illumina and Oxford Nanopore Technologies platforms, respectively. Hybrid assembly led to their complete genome sequences, which revealed diverse genes mediating antimicrobial resistance, heavy metal resistance and virulence, some of which were located on plasmids. All four M. sciuri genomes also harboured unique and non-typeable staphylococcal cassette chromosome mec (SCCmec) elements that encode the mecA gene which mediate resistance to β-lactams. Phylogenetic analysis indicated significant diversity within the Malaysian M. sciuri isolates and identified close genetic relationships with global isolates from various sources, including humans, suggesting potential cross-species transmission. These findings provide valuable genomic insights into M. sciuri from Malaysia and underscore the importance of genomic surveillance in tracking the emergence and dissemination of AMR in this opportunistic pathogen.